Outpatient metformin use is associated with reduced severity of COVID‐19 disease in adults with overweight or obesity. Issue 7 (23rd March 2021) - Bramante, Carolyn T.; Buse, John; Tamaritz, Leonardo; Palacio, Ana; Cohen, Ken; Vojta, Deneen; Liebovitz, David; Mitchell, Nia; Nicklas, Jacinda; Lingvay, Ildiko; Clark, Jeanne M.; Aronne, Louis J.; et al.
Abstract: Observational studies suggest outpatient metformin use is associated with reduced mortality from coronavirus disease‐2019 (COVID‐19). Metformin is known to decrease interleukin‐6 and tumor‐necrosis factor‐α, which appear to contribute to morbidity in COVID‐19. We sought to understand whether outpatient metformin use was associated with reduced odds of severe COVID‐19 disease in a large US healthcare data set. Retrospective cohort analysis of electronic health record (EHR) data that was pooled across multiple EHR systems from 12 hospitals and 60 primary care clinics in the Midwest between March 4, 2020 and December 4, 2020. Inclusion criteria: data for body mass index (BMI) > 25 kg/m 2 and a positive SARS‐CoV‐2 polymerase chain reaction test; age ≥ 30 and ≤85 years. Exclusion criteria: patient opt‐out of research. Metformin is the exposure of interest, and death, admission, and intensive care unit admission are the outcomes of interest. Metformin was associated with a decrease in mortality from COVID‐19, OR 0.32 (0.15, 0.66; p = .002), and in the propensity‐matched cohorts, OR 0.38 (0.16, 0.91; p = .030). Metformin was associated with a nonsignificant decrease in hospital admission for COVID‐19 in the overall cohort, OR 0.78 (0.58–1.04, p = .087). Among the subgroup with a hemoglobin HbA1c available ( n = 1193), the adjusted odds of hospitalization (including adjustment for HbA1c) for metformin users was OR 0.75 (0.53–1.06, p = .105). Outpatient metformin use was associated with lower mortality and a trend towards decreased admission for COVID‐19. Given metformin's low cost, established safety, and the mounting evidence of reduced severity of COVID‐19 disease, metformin should be prospectively assessed for outpatient treatment of COVID‐19. Highlights: Oral outpatient therapies for SARS‐CoV‐2 infection are desperately needed. Metformin has a history of anti‐inflammatory and anti‐viral effects. In this retrospective cohort analysis in persons with overweight or obesity outpatient metformin use was associated with lower lower mortality. There was no significant association with reduced hospitalization.